Tingkat Kepentingan Faktor Penyesuaian Non-Transaksional dalam Penilaian Tanah Berdasarkan Persepsi Penilai Pemerintah - Warlan Warlan; M. As'ad Firdaus; I Wayan Mardana (Polytechnic of State Finance STAN, 2022)
One of the processes in the valuation analysis using the market approach is the adjustment of the comparison object data. Adjustments are made to transactional and non-transactional factors. For non-transactional factors including location, land area, land shape, soil type, land contour, elevation from the road surface, accessibility, and facilities. This study aims to determine the level of importance of the non-transactional adjustment factor on the value of residential, commercial, industrial, agricultural, and plantation land based on the perceptions of government appraisers at DGSAM. This research was conducted to see the perception of government appraisers at the national level, island clusters, and regional office clusters. The results of the national research show that the most influential factor on the value of residential land and commercial land is the location factor. The value of industrial land is most influenced by the accessibility factor, while agricultural land and plantation land are most influenced by the land area factor.